PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRADING PLACE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI SMA PGRI 1 PADANG - Devina, Reza; Rahmi, Rahmi; Suryani, Mulia (STKIP PGRI Sumbar, 2014)
Â ABSTRACTThis research was conducted due to the studentâs low understanding on mathematics concept. This was aimed at revealing whether the use of Trading Places active learning strategy could improve the studentsâ understanding on mathematics concept better than that of the conventional one in class XI IPS of SMA PGRI 1 Padang. This was an experimental research. The population of the research was the students in class XI registered in Academic Year 2013/2014. The instrument of the research was an essay test whose reliability was 0,836. The result of data analysis indicated the average score of the studentsâ understanding on mathematics concept in experimental class was 60,04 and in the control class was 48,96. As the result of hypothesis test showed that P-value < Î±, H0 was rejected and H1 was accepted. Thus, the use of Trading Places active learning strategy could improve the studentsâ understanding on mathematics concept better than that of the conventional one in class XI IPS of SMA PGRI 1 Padang.Â